IN DEFENSE OF CULTURE: COMMUNIST INTELLECTUALS AND LITERARY MAGAZINES IN THE 1930S. - Amelia de Melo, Ana (Revista de Historia Social y de las Mentalidades, 2022)
The objective of this article is to conduct a comparative examination between the Brazilian literary newspaper Dom Casmurro (1937-1946) and the Chilean publication Aurora de Chile (1938-1940). Both periodicals not only had outstanding communist intellectuals such as Jorge Amado, editor-in-chief of the Brazilian newspaper between 1939-1940, and Pablo Neruda, creator and director of Aurora de Chile, but also sought to express the popular front project proposed by the Communist International in the fight against fascism. I seek here to examine how these publications crystallized some ideas of defense of culture, the role of intellectuals as militants, and the distinct strategies of communists in the face of the singularities of political experiences in Latin America. Methodologically, the publications are approached as documents of culture that expressed a collective political-cultural project.